The role of astrocytes in neuropathic pain - Cheng, Tong; Xu, Zhongling; Ma, Xiaqing (Frontiers in Molecular Neuroscience, 2022)
Neuropathic pain, whose symptoms are characterized by spontaneous and irritation-induced painful sensations, is a condition that poses a global burden. Numerous neurotransmitters and other chemicals play a role in the emergence and maintenance of neuropathic pain, which is strongly correlated with common clinical challenges, such as chronic pain and depression. However, the mechanism underlying its occurrence and development has not yet been fully elucidated, thus rendering the use of traditional painkillers, such as non-steroidal anti-inflammatory medications and opioids, relatively ineffective in its treatment. Astrocytes, which are abundant and occupy the largest volume in the central nervous system, contribute to physiological and pathological situations. In recent years, an increasing number of researchers have claimed that astrocytes contribute indispensably to the occurrence and progression of neuropathic pain. The activation of reactive astrocytes involves a variety of signal transduction mechanisms and molecules. Signal molecules in cells, including intracellular kinases, channels, receptors, and transcription factors, tend to play a role in regulating post-injury pain once they exhibit pathological changes. In addition, astrocytes regulate neuropathic pain by releasing a series of mediators of different molecular weights, actively participating in the regulation of neurons and synapses, which are associated with the onset and general maintenance of neuropathic pain. This review summarizes the progress made in elucidating the mechanism underlying the involvement of astrocytes in neuropathic pain regulation.